1994
DOI: 10.1007/bf01377124
|View full text |Cite
|
Sign up to set email alerts
|

An updated review of the clinical development of coumarin (1,2-benzopyrone) and 7-hydroxycoumarin

Abstract: Several authors have demonstrated that coumarin (1,2-benzopyrone) in combination with cimetidine can produce objective antitumor responses in some patients with advanced renal cell carcinoma. The purpose of this report is to review the clinical development of coumarin, with or without cimetidine, with special reference to renal cell carcinoma (RCC). Previously unpublished data concerning the survival of a population of patients with RCC, who were treated on a phase I trial of coumarin and cimetidine, are prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(43 citation statements)
references
References 10 publications
1
38
0
Order By: Relevance
“…The estimates for the slopes by group are provided in the Table 1. For example, tumor volumes were significantly reduced from 500 Ϯ 401 mm 3 in the controls to 195 Ϯ 172 mm 3 in tumors that had a single injection of dicumarol 100 M (P Ͻ 0.001 versus controls, means Ϯ SD).…”
Section: Dicumarol Decreases Cell Viability and Clonogenicmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimates for the slopes by group are provided in the Table 1. For example, tumor volumes were significantly reduced from 500 Ϯ 401 mm 3 in the controls to 195 Ϯ 172 mm 3 in tumors that had a single injection of dicumarol 100 M (P Ͻ 0.001 versus controls, means Ϯ SD).…”
Section: Dicumarol Decreases Cell Viability and Clonogenicmentioning
confidence: 99%
“…Coumarin, the parent molecule of dicumarol, and a variety of coumarin compounds have demonstrated numerous antitumor and antiproliferative effects. Coumarin compounds have been shown to inhibit proliferation of particular human malignant cell lines in vitro (3)(4)(5)(6)(7)(8), as well as affecting tumor activity against several in vivo tumor types (1, 9 -13). In clinical trials, these compounds have also been demonstrated to have some activity against prostate cancer, malignant melanoma, and metastatic renal cell carcinoma (14 -16).…”
Section: Introductionmentioning
confidence: 99%
“…Coumarin has also been used clinically at high dosages in humans in the treatment of high-protein lymphedemas (Jamal and Casley-Smith, 1989) and as an antineoplastic agent in the treatment of renal cell carcinoma (Marshall et al, 1994) and malignant melanoma (Marshall et al, 1989). Although reports of adverse effects in humans resulting from coumarin treatment are rare (Cox et al, 1989;Egan et al, 1990), administration of coumarin to rodents produces rat liver (Lake, 1984;Lake et al, 1989) and mouse lung toxicity (Born et al, 1998).…”
mentioning
confidence: 99%
“…Compounds with these ring system have diverse pharmaceutical activities such as antioxidant, antimicrobial, anticoagulant, anti-HIV, antithrombotic, antieancer, enzyme inhibitory, urease inhibitory and cytotoxicity [8][9][10][11][12][13][14][15][16] . A number of biscoumarins are useful as malignant melanoma, metastatic renal cell carcinoma and prostate cancer drugs [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%